Comprehensive Study of Factors Affecting e-Learning Participant Satisfaction: A Study on Online Pendidikan Profesi Guru at Ibn Khaldun Bogor University - Zachary, Achmad Shafly; Palupi, Majang (Jurnal Manajemen (Edisi Elektronik), 2024)
E-learning has evolved from being optional to indispensable in contemporary education due to advancements in technology and the evolving educational landscape. The growth trajectory of e-learning is poised to accelerate further, with projections indicating a user base of approximately 21.6 million by 2029. This study examines the environmental factors of e-learning that influence participant satisfaction in the Pendidikan Profesi Guru (PPG) Program at Ibn Khaldun University Bogor that is held via e-learning, currently conducted with 147 respondents. This research employed a quantitative method with nine variables, including one dependent variable, participant satisfaction in e-learning, and eight independent variables representing factors affecting satisfaction. Data were analysed using Partial Least Squares (PLS) and multiple linear regression analysis. The study found that all independent variables positively influence partici-pant satisfaction in e-learning, with 4 variables significantly af-fecting satisfaction: e-learning flexibility, technology quality, in-ternet quality, and interaction in the e-learning environment. The implications of this study extend beyond the PPG Program, suggesting relevance to other educational and training initiatives conducted via e-learning. Researchers propose further exploration of additional influencing factors to enhance the comprehensiveness of future studies. In conclusion, as e-learning continues to gain prominence, addressing the identified environmental factors becomes crucial for insti-tutions striving to deliver high-quality educational experiences. By adapting to these insights, educational providers can better meet the diverse needs of learners in the digital era, thereby fostering an inclusive and effective learning environment conducive to en-hanced participant satisfaction and educational outcomes.